Społeczność pochodzenia ukraińskiego a Warmii i Mazurach po 1947 roku. Jej wpływ na rozwój kulturalny regionu północno-wschodniej Polski - Wrzosek, Paweł (Acta Polono-Ruthenica, 2006)
The community of Ukrainian origin in Warmia and Mazury is not often the object of research due to the fact that it is strongly involved in ideology and politics, which makes it difficult to draw a boundary between propaganda and its actual problems. What contributed to the transformation of the Ukrainian culture into the North-East Poland were activities of those Ukrainian communities that migrated into this region in the course of „Wisła” action in 1947. The research that the author conducted in a group of Ukrainian teenagers in 2004 casts a new light onto the community, making it possible to characterize the continuously evolving problems of its existence. The approach to this topic highlights the way in which the Ukrainian minority, tom apart from its original environment, deals with its problems and is gradually integrating into the new reality. It also focuses on the analysis of differences concerning mutual relations. In time. the awareness of the Ukrainian community members has lost its demanding nature, and has become filled with invention and initiative, thus resembling the awareness that the hosts of their new motherland should display. It is very interesting to notice that the Poles are often participants in the cultural events organized by the Ukrainians.